Conductas Delictivas Y Antisociales En Adolescentes Que Estudian Y No Estudian - Palencia, Angélica Romero; Solís, Araceli Sánchez; Arreola, Arturo del Castillo (European Scientific Journal, ESJ, 2017)
Adolescence is a stage of transition from childhood to the adult world, which is affected among other things by the tension between the incorporation into the labor market and permanence in the educational system (D’alessandre, 2010). However, there is little information related to adolescents who do not study or work. Because of the information that antisocial and criminal behavior tends to accentuate at this stage of life (Gaeta & Galvanoski, 2011), this study identifies differences in the presence of antisocial and criminal behavior among students in two public high schools at Pachuca Hidalgo, Mexico, and adolescents who do not study or work in the same city using the AD measure (Seisdedos & Sánchez, 2001). The sample consisted of 120 teenagers between 14 and 18 years of age, with a total of 81 students and 39 adolescents who do not study or work. Through an analysis of variance ANOVA of sex by occupation were found significant differences in the presence of antisocial behaviors between adolescents who study and those who do not. A difference was observed in the presence of criminal behavior also, specifically in the group of male adolescents who did not study. It was observed that those adolescent men and women who are studying, are less likely to commit criminal acts, compared to those adolescent especially men who are not within a school or work system. The role played by the socio-cultural context as a risk factor or protection for the appearance of criminal and antisocial behavior is highlighted.